The Role of Local Indigenous Communities in Responding to Climate Change Through Community Development Program - Utami, Dyah Putri; Imawan , Bambang; Saputra, Ferdy (Indonesian Journal of Social Responsibility Review (IJSRR), 2024)
Indigenous people are one of the communities affected by global climate change. As a group of people who depend on nature to meet their daily needs, increasingly erratic weather changes are one of the factors that change the pattern of meeting their needs. In addition, as one of the communities at the site level, indigenous communities have a fairy high vulnerability index to climate change. One of the indigenous communities affected by climate change in Moi Lemas Tribal community who inhabit District Seget, Sorong Regency. Therefore, strategies are needed to respond to the impacts of climate change among indigenous communities. To increase the capacity to adapt and mitigate climate change to The Moi Lemas tribal community group, 10 local groups called The ProKlim (Program Kampung Iklim) groups were formed which are spread across 10 villages and hamlets in District Seget since 2022. It is known that the program implemented by ProkLim group succeeded in reducing the vulnerability index of the indigenous Moi Lemas tribe in District Seget to level 8, from before the program it was at level 14.